2017
DOI: 10.1177/1753425917698032
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and the hypoxia-regulated transcription factor HIF-1α suppress the host defence of airway epithelial cells

Abstract: Chronic diseases of the respiratory tract, such as cystic fibrosis, are associated with mucosal and systemic hypoxia. Innate immune functions of airway epithelial cells are required to prevent and control infections of the lung parenchyma. The transcription factor hypoxia-inducible factor 1a (HIF-1a) regulates cellular adaptation to low oxygen conditions. Here, we show that hypoxia and HIF-1a regulate innate immune mechanisms of cultured human bronchial epithelial cells (HBECs). Exposure of primary HBECs to hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 49 publications
0
29
1
1
Order By: Relevance
“…Airway epithelial cells (AECs) are the initial checkpoints in the defence against pathogens and other inhaled particulates, and these cells are crucial to the regulation of both innate and adaptive immune responses to these challenges [52,53].…”
Section: Airway Epithelial Cellsmentioning
confidence: 99%
“…Airway epithelial cells (AECs) are the initial checkpoints in the defence against pathogens and other inhaled particulates, and these cells are crucial to the regulation of both innate and adaptive immune responses to these challenges [52,53].…”
Section: Airway Epithelial Cellsmentioning
confidence: 99%
“…Hypoxia promotes the B cell differentiation potential of lymphoid-primed multipotent progenitors through HIF-1α, resulting in the production of B cells (97). Under hypoxic conditions, HIF-1α also regulates innate immune responses, induces regulatory T cells (Tregs), and mediates immune escape from cytotoxic T lymphocytes and other complex immune responses (98)(99)(100). In previous years, HIF-1α-mediated tumor immunity has been proposed as a direction to solve the problems associated with tumor therapy (101)(102)(103), so the immune response of CSCs mediated by HIF-1α is also worth exploring when investigating antitumor therapies.…”
Section: Role Of Hif-1 In Tumor Immunity Of Cscsmentioning
confidence: 99%
“…In addition to H/R, consecutive hypoxia for a long period has also been reported to modulate the inflammatory functions and oxidant-induced cell injury in airway epithelial cells (Olson et al, 2011;Pahlman et al, 2015;Pandya et al, 2016;Polke et al, 2017). It was shown that consecutive hypoxia for longer than 24 h contributed to the pathogenesis of chronic pulmonary diseases via both the HIF1α-dependent downregulation of the complement regulatory protein CD55 and several inflammatory cytokines, including IL-6, IP-6, IP-10, and hBD-2, as well as the TGFβ1-dependent downregulation of the secretory leukocyte protease inhibitor, in human airway epithelial cells (Pahlman et al, 2015;Pandya et al, 2016;Polke et al, 2017).…”
Section: Introductionmentioning
confidence: 99%